The Effect Of Applying Cooperative Learning Method By Using Media Tayang On The Students’ Writing Achievement - Rizky Maylani (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2022)
The objectives of the research were to find out the effect of applying cooperative learning by using media tayang on the students’ writing achievement. The research was conducted at SMP Muhammadiyah 57 Medan located in Jalan Mustafa No.1 Kecamatan Medan Timur. The population was 2019/2020 year. The sample was taken from two classes of  population which had three classes. The students were divided into two groups, they were pre-test and post-test. The experimental group there were 28 students which taught by applying cooperative learning method by using media tayang on the students’ writing achievement and the control group there were 28 students which taught by using conventional method. The instrument was used by writing test. In scoring of the students’ writing achievement there were five categories content, organization, vocabularies, language use, and mechanism. The data was analyzed by using t-test  formula. The finding showed that the t-hitung value was higher that t-table was 22 and 1.673 ( 22 1.673 ). It means that the null hypothesis ( Ho ) was rejected and the alternative hypothesis ( Ha ) was accepted .